Prone Positioning in Acute Respiratory Distress Syndrome - Gattinoni, Luciano; Busana, Mattia; Giosa, Lorenzo; Macrì, Matteo Maria; Quintel, Michael (Seminars in Respiratory and Critical Care Medicine, 2019)
Prone positioning is nowadays considered as one of the most effective strategies for patients with severe acute respiratory distress syndrome (ARDS). The evolution of the pathophysiological understanding surrounding the prone position closely follows the history of ARDS. At the beginning, the focus of the prone position was the improvement in oxygenation attributed to a perfusion redistribution. However, the mechanisms behind the prone position are more complex. Indeed, the positive effects on oxygenation and CO2 clearance of the prone position are to be ascribed to a more homogeneous inflation–ventilation, to the lung/thoracic shape mismatch, and to the change of chest wall elastance. In the past 20 years, five major trials have tried, starting from different theories, hypotheses, and designs, to demonstrate the effectiveness of the prone position, which finally found its definitive place among the different ARDS supportive therapies.
Keywords: Acute Respiratory Distress Syndrome; ARDS; prone position; trial design; oxygenation; shape mismatch; chest wall elastance